ANALISIS TINGKAT PENDIDIKAN DAN PARITAS IBU BERSALIN DENGAN PEMILIHAN TEMPAT PERSALINAN DI DESA PEMANTANG WILAYAH KERJA PUSKESMAS KUALA KUAYAN TAHUN 2019 - puspita sari pribadi (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2020)
ABSTRACT Background : The biggest effort in the health sector is to reduce the Maternal Mortality Rate (MMR) with the target of Sustainable Development Goals (SDGs) in 2030, namely 70 per 100.000 KH and not more than 140, because for any country MMR is still a health problem. around the world (WHO, 2015), Based on data from the Indonesian Health Demographic Survey (2007), in 2015 the MMR had decreased to 305 maternal deaths per 100,000 live births (WHO, 2015). Maternal mortality is closely related to the helper and the place of delivery. Deliveries assisted by trained health personnel are a key factor in reducing maternal mortality (WHO, 2015). Objectives : To determine the relationship between education level and maternal parity with the choice of place of delivery at the in Pemantang village working area of health center Kuala Kuayan year 2019 Methods : This study used an analytical method with a retrospective design. This was carried out at the Pemantang Village in the Kuala Kuayan Health Center Work Area in 2019 with a sample of 39 people who used the Totally Sampling technique from secondary data. Results : The results of the bivariate analysis using the chi-square test and fisher's exact test from 39 samples, there is a significant relationship between the education level variable and the choice of place of delivery at the Pemantang Desa value: 0.006 (<0.05) and from 39 samples there is no significant relationship between the parity variable with the choice of place of delivery at value: 0.153 (> 0.05). Conclusion : The analysis of Education Level and Maternal Parity with the Choice of Place of Delivery.